## Simplifying (9u)^2

The expression **(9u)^2** represents the square of the entire quantity **9u**. Let's break down how to simplify it without parentheses.

### Understanding the Concept

Remember that squaring a term means multiplying it by itself. So, (9u)^2 is equivalent to:

**(9u)^2 = (9u) * (9u)**

### Applying the Rules of Exponents

When multiplying terms with exponents, we add the exponents. In this case, both **9** and **u** have an implied exponent of **1**. Applying this rule:

**9^1 * 9^1 = 9^(1+1) = 9^2****u^1 * u^1 = u^(1+1) = u^2**

### The Final Result

Combining these results, we get:

**(9u)^2 = 9^2 * u^2 = ** **81u^2**

Therefore, **(9u)^2** without parentheses is equivalent to **81u^2**.